Engaging Possibilities: Reinvigorating the Call for Research on Reading. (November 2019) - Ivey, Gay
Can we teach children and young adults about reading while simultaneously and inseparably teaching them how to take control of their own lives and relationships, a possibility that has been just barely touched by research and even less so by educational policies and practice? This address highlights research findings that suggest the promise of literacy engagement for clarifying and expanding how we think about reading assessment, achievement, comprehension, socio-emotional growth, and equity in literacy instruction. Using my own evolution as a researcher studying, primarily, the classroom-based reading experiences of middle school students, I show how my own questions and theoretical perspectives shifted based on what the children taught me as I studied their experiences and how that led me to champion engagement as a promising way forward. I rely heavily on what students themselves have shared with me, as their perspectives have fueled the shifts in my thinking and in the research questions I have pursued. I then share what I believe is the potential of an engagement-focused perspective on our field's knowledge about reading development and practices. Finally, I comment on what we might need to do to make this line of research influence real classrooms and policies in positive ways. I argue that in order to influence, through an engagement perspective, the transformation of reading-related policies—and more importantly the agentive transformation of individuals and communities—we must renew our commitment to research conducted in classrooms and in partnership with teachers and families.